General Considerations on the Biosafety of Virus-derived Vectors Used in Gene Therapy and Vaccination - Baldo, Aline; van den Akker, Eric; E. Bergmans, Hans; Lim, Filip; Pauwels, Katia (Current Gene Therapy, 2013)
This introductory paper gathers general considerations on the biosafety of virus-derived vectors that are used in human gene therapy and/or vaccination. The importance to assess the potential risks for human health and the environment related to the use of genetically modified organisms (GMO) in this case genetically modified viral vectors is highlighted by several examples. This environmental risk assessment is one of the requirements within the European regulatory framework covering the conduct of clinical trials using GMO. Risk assessment methodologies for the environmental risk assessment of genetically modified virus-derived vectors have been developed.
Keywords: gene therapy